Analisis pengaruh fraud diamond terhadap potensi kecurangan program bantuan langsung tunai dana desa kabupaten jombang - Sholawati, Alvin; Bhilawa, Loggar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study was conducted with the aim of knowing the effect of Fraud Diamond elements which include pressure, opportunity, rationalization, and capability on the potential for fraud in the village fund program in Jombang Regency, East Java. This research uses quantitative methods, sources of data in this study were obtained from primary data sources by distributing questionnaires to village heads and village officials in Jombang Regency who came from Jombang District, Mojoagung District, Peterongan District, and Diwek District. The total population of this study was 1,510 with a total of 315 samples and was selected using cluster random sampling technique. The data analysis technique is using multiple linear regression with the help of the IBM SPSS 23 application program. The hypothesis in this study is that the Fraud Diamond Theory element consisting of pressure, opportunity, rationalization, and capability has an influence on the potential for fraud in village funds in Jombang Regency. The test results show that all hypotheses are accepted, namely the Fraud Diamond Theory element affects the potential for fraud in the village fund program in Jombang Regency.